Closing the multichannel gap through computational reconstruction of interaction in super-resolution microscopy - Ben Cardoen; Hanene Ben Yedder; Ivan Robert Nabi; Ghassan Hamarneh (Patterns)
Summary: Cellular function is defined by pathways that, in turn, are determined by distance-mediated interactions between and within subcellular organelles, protein complexes, and macromolecular structures. Multichannel super-resolution microscopy (SRM) is uniquely placed to quantify distance-mediated interactions at the nanometer scale with its ability to label individual biological targets with independent markers that fluoresce in different spectra. We review novel computational methods that quantify interaction from multichannel SRM data in both point-cloud and voxel form. We discuss in detail SRM-specific factors that can compromise interaction analysis and decompose different classes of interactions based on distinct representative cell biology use cases, the underappreciated non-linear physics of their scale, and the development of specialized methods for those use cases. An abstract mathematical model is introduced to facilitate the comparison and evaluation of interaction reconstruction methods and to quantify the computational bottlenecks. We discuss the different strategies for validation of interaction analysis results with sparse or incomplete ground-truth data. Finally, evolving trends and future directions are presented, highlighting the “multichannel gap,” where interaction analysis is trailing behind the rapid increase in novel modes of multichannel SRM acquisitions. The bigger picture: Discovering how, where, and when interactions between proteins and organelles work is critical to unravel the molecular and cellular basis of cancer, metabolic, and degenerative diseases and how drugs can intervene. Super-resolution microscopy (SRM) is uniquely positioned to discover these interactions. We review novel interaction-analysis algorithms, and we identify specific SRM factors that can compromise the accuracy of interaction analysis. To evaluate these and future approaches, we introduce a mathematical framework, simplifying evaluation of existing and future algorithms. We highlight the “multichannel gap,” where interaction analysis finds itself lagging behind the rapid innovations in novel multichannel SRM microscopes, and review validation strategies. We offer cell biologists a gateway to quickly identify which method is needed to accurately discover complex interactions in the cell, opening new avenues for more precise drug discovery.